Spectrophotometric Determination of Alendronate Sodium in Bulk Drug and in Pharmaceutical Formulation - A. Alarfaj , Nawal; A. Abd El-Razeq, Sawsan; N. Al-Qahtani, Fatma (Asian Journal of Chemistry, 2011)
A sensitive, simple, precise and low-cost spectrophotometric method for alendronate sodium (ALD) determination has been proposed. The procedure is based on the reaction of the primary amino group of alendronate sodium with ninhydrin reagent in a boiling water bath in presence of pyridine to yield a bluish-violet product measured at 565 nm. Linear calibration curve was obtained in the range 1-60 μg/ mL, with minimum detectability of 0.1 μg/mL. The correlation coefficient was 0.9999 (n = 7). The different experimental parameters have been carefully studied. The proposed method has been successfully applied to the analysis of the studied drug in pure form and in commercial tablets. The average percentage recovery (n = 7) was 99.8 ± 0.35. The results were compared statistically with those obtained from a published method as revealed by t- and F- tests.